2016
DOI: 10.1038/nature17958
|View full text |Cite
|
Sign up to set email alerts
|

Lightwave-driven quasiparticle collisions on a subcycle timescale

Abstract: Ever since Ernest Rutherford first scattered α-particles from gold foils1, collision experiments have revealed unique insights into atoms, nuclei, and elementary particles2. In solids, many-body correlations also lead to characteristic resonances3, called quasiparticles, such as excitons, dropletons4, polarons, or Cooper pairs. Their structure and dynamics define spectacular macroscopic phenomena, ranging from Mott insulating states via spontaneous spin and charge order to high-temperature superconductivity5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
211
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(220 citation statements)
references
References 49 publications
7
211
1
1
Order By: Relevance
“…The HHG has resulted in the birth of attosecond (1 as = 10 −18 s) pulses [4,5] and new imaging tools, such as molecular tomography [6] and spectroscopy [7]. Recent experiments have demonstrated that light-solid interactions offer a wide range of other phenomena and applications to be explored [8][9][10], including HHG from solid-state materials [11][12][13][14][15].Experimental results present a recollision feature in two-color laser fields [16], which is similar to HHG from the gas phase. However, it is also found that the cutoff of HHG from the solid phase depends on the strength E 0 of the laser fields linearly [11], rather than quadratically in the gas phase.…”
mentioning
confidence: 99%
“…The HHG has resulted in the birth of attosecond (1 as = 10 −18 s) pulses [4,5] and new imaging tools, such as molecular tomography [6] and spectroscopy [7]. Recent experiments have demonstrated that light-solid interactions offer a wide range of other phenomena and applications to be explored [8][9][10], including HHG from solid-state materials [11][12][13][14][15].Experimental results present a recollision feature in two-color laser fields [16], which is similar to HHG from the gas phase. However, it is also found that the cutoff of HHG from the solid phase depends on the strength E 0 of the laser fields linearly [11], rather than quadratically in the gas phase.…”
mentioning
confidence: 99%
“…(Please note that the radiative lifetime is considered to be much longer than this value [62]). This is much shorter than the pulse width of the driving laser used in the experiments ( 100 fs) [27]. As long as the pulse width of the driving field is longer than the lifetime of the excited state, the HHG spectrum does not depend on its pulse width.…”
Section: Discussionmentioning
confidence: 94%
“…We take these parameters to approximately represent the experiments of WSe 2 , such as the driving laser field frequency 2π/ω 20 THz, the band gap between the valence and the conduction bands ∆ 0 400 THz [27]. The driving laser amplitude a ≡ A/ω is determined so as to agree with the cutoff energy of the experiments n cutoff /hω 10.…”
Section: Hhg Spectrummentioning
confidence: 99%
See 2 more Smart Citations